Kajian Valuasi Ekonomi Lahan Rawa Gambut di Sekitar Kawasan Industri Gasing di Kecamatan Talang Kelapa Kabupaten Banyuasin Provinsi Sumatera Selatan - Arby, Muhammad; Sriati, Sriati; Yamin, M.; Tertiarto, Tertiarto (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Arbi, M., Sriati, S., Yamin, M., Tertiarto, T. (2024). Analysis of the value of environmental services in the existence of peat swamp forests around the gasing industrial area in Talang Kelapa District, Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 969–975). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). This study focuses on efforts to find and understand the environmental services and economic value of the existence of peat swamp land around the gasing industrial area through a comprehensive approach in the Gasing Village area, Talang Kelapa District, Banyuasin Regency. The aimed of this research is to identify direct and indirect benefits and calculate the economic value of peat swamp land in the Gasing industrial area in Gasing Village, Talang Kelapa District, Banyuasin Regency. Data collection was obtained from secondary and primary data including observation and interviews. Interviews were conducted with stakeholders including business actors, government and the surrounding community with 200 respondents. The results of the study indicate that the environmental services of the existence of peat swamp land in the industrial area have direct benefits as a place for fish breeding and producing gelam wood with an average value of IDR 118,545,538 per year. Meanwhile, indirect benefits include water absorption, biodiversity, and recreation with an average value of 1,387,475,165 per year. The total economic value of the existence of peat land in the gasing industrial area is 8,324,849,990 per year.